Analisa Proses Editing Video Berita Menggunakan Software Edius Dan Adobe Premiere Pada Pasca Produksi Untuk Program Televisi Di PT. Indrasakti Media Televisi - Fahri Arieffansyah (Pusat Riset dan Inovasi Nasional, 2023)
The analysis of this study is to provide a good overview of the advantages and disadvantages of the two video editing platforms, namely Edius and Adobe Premiere, in the context of the news video editing process in post-production. The analysis also highlights that the decision to choose between the two comes down to user preference, whether they prefer a broad feature set or a more seamless editing experience. The last comments have provided clear recommendations to users with different needs. Users who need a lot of features tend to prefer Adobe Premiere, while those who prefer agility and fluency in the editing process may prefer Edius.